Impact of ICT and Curriculum Development (University Students from Nigeria) using Modified Technology Acceptance Model -TAM - Memoye Kepeghom, Oruan; Cruz Antony, J; Ipeghan Godpower, Igenewari; Tamunoibuomi, Richard (International Journal of Computer Sciences and Engineering, 2025)
The Education system is taking a new dimension, the ICT based teaching and learning. ICT is one of the contemporary factors which shapes the education system and has the ability to transform the system of education. To study the impact of ICT, acceptance level from the measure of intention of the users (i.e. students) has to be surveyed. Hence, Technology Acceptance Model (TAM) is used with the introduction of a latent variable for improvisation within the university settings. Data is collected using questionnaire, which is prepared to keep in mind all the variables in TAM. Various machine learning techniques have been imposed on the dataset and found that Decision tree has exhibited high accuracy in classification. The results prove that the factors impacting on user acceptance are availability of ICT, perceived ease of use, perceived impact in teaching & learning, perceived inhibitors in teaching & learning and perceived pleasure or arousal, availability, and inhibitor to use the system, which is also affected by inhibitors in the use of ICTs in the universities.